准端面双圆弧齿轮及其齿面方程 - 段德荣; 常彦伟 (Jixie chuandong)
Theory of quasi-circular-arc gear’s shaping is discussed in this paper, and its common tooth-surface equation is developed. By the graphic spectrum analysis of the profiles in end section, especially by contrast with the normal circular-arc gear universally employed at present and ideal contrate circular-arc gear, its unique advantage of overcoming deviation sensitiveness is pointed out. This always occurred at the contact region of the normal circular-arc gear’s engaging. It’s work process isn’t difficult at all, since a hobbing cuter can work on gears with different helix angles.